2015
DOI: 10.1136/bjophthalmol-2015-307599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcome of tuberculous sclerokeratitis

Abstract: Antituberculous medications can lead to complete resolution of the sclerokeratitis without concomitant use of steroids, or other anti-inflammatory agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Though tuberculous keratoscleritis has been known as a common differential in endemic countries, it has been often noted as scleral abscess and necrosis and not been observed as isolated corneal endothelial opacity. [ 7 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though tuberculous keratoscleritis has been known as a common differential in endemic countries, it has been often noted as scleral abscess and necrosis and not been observed as isolated corneal endothelial opacity. [ 7 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The common morphological changes on the cornea induced by anterior scleritis are astigmatism, sclerokeratitis, limbitis, and peripheral ulcerative keratitis (PUK). [ 6 7 8 ] In 1976, Watson et al . [ 9 ] described about 29% of anterior scleritis causing corneal changes predominantly involving the anterior and the stromal layers of cornea.…”
mentioning
confidence: 99%
“…A study by Wroblewski suggested that longstanding tuberculous ocular infections can produce corneoscleral perforations [7]. Shoughy et al treated all the 8 patients having scleritis with a minimum of 6 months of antitubercular drugs without concomitant use of corticosteroid and the complete resolution was seen [8].…”
Section: Discussion:-mentioning
confidence: 99%
“…[3,8] Intraocular findings suggestive for the diagnosis of ocular sarcoidosis include conjunctival nodules, keratic precipitates, episcleritis, iris nodules, peripheral anterior synechiae, vitreous opacities, choroidal granulomas, retinal vasculitis, and optic disc nodules. [8][9][10] The choroid consists of a network of capillaries and larger choroidal vessels. The choroid, which is the most vascular structure of the eye, is affected by many systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Uveitis, the sight threatening complication, can be diagnosed up to 20% to 30% of patients during the course of the disease [3,8] . Intraocular findings suggestive for the diagnosis of ocular sarcoidosis include conjunctival nodules, keratic precipitates, episcleritis, iris nodules, peripheral anterior synechiae, vitreous opacities, choroidal granulomas, retinal vasculitis, and optic disc nodules [8–10] …”
Section: Introductionmentioning
confidence: 99%